Network effects, market structure and industry performance - Rabah Amir; Natalia Lazzati (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
This paper provides a thorough analysis of oligopolistic markets with positive demand-side network externalities and perfect compatibility. The minimal structure imposed on the model primitives is such that industry output increases in a firm's rivals' total output as well as in the expected network size. This leads to a generalized equilibrium existence treatment that includes guarantees for a nontrivial equilibrium, and some insight into possible multiplicity of equilibria. We formalize the concept of industry viability and show that is it always enhanced by having more firms in the market and/or by technological improvements. We also characterize the effects of market structure on industry performance, with an emphasis on departures from standard markets. The approach relies on latticetheoretic methods, which allow for a unified treatment of various general results in the literature on network goods. Several illustrative examples with closed-form solutions are also provided.
Keywords: C72; D43; L13; L14; 330; Network effects; demand-side externalities; monotone comparative statics; Cournot oligopoly; supermodularity